Detection, cloning, and distribution of minisatellites in some mammalian genomes. - Vergnaud, G; Gauguier, D; Schott, J; Lepetit, D; Lauthier, V; Mariat, D; Buard, J (1993)
The chromosomal distribution of minisatellites (cloned and/or detected using natural or synthetic tandem repeats) is strikingly different in man and mouse. In man, the vast majority is clustered in the terminal band of a subset of chromosome arms. Interestingly, the class of shorter tandem repeats called microsatellites is widespread along the chromosomes, suggesting that minisatellites can be created or maintained only in certain regions. In order to gain a better knowledge of these areas, we have studied a sub-telomeric cosmid from the pseudoautosomal region. Sixty kilobases of human genomic DNA starting approximately 20 kilobases from the human sex chromosomes telomere have previously been independently isolated in two cosmid clones (locus DXYS14) (Cooke et al., 1985); Rouyer et al., 1986). We have studied in more detail one of the two cosmids from this locus and found that it contains four different minisatellite structures representing 20 kilobases of the cosmid. These structures are unrelated to each other or to the minisatellite family described by Jeffreys et al. (1985). They display different degrees of polymorphism correlated with varying amounts of inner homogeneity. Combined with the previous description of an additional minisatellite (Cooke et al., 1985; Inglehearn and Cooke, 1990) in the contiguous cosmid, our observation shows that these structures may represent an important proportion of the DNA in sub-telomeric regions.